Improvement of sports technique based on biomechanical indicators of yurchenko handspring vault in women's artistic gymnastics - Potop, V.; Dorgan, V.; Jurat, V. (European Journal of Interdisciplinary Studies, 2017)
The main purpose of this paper is the biomechanical analysis of the kinematic and dynamic indicators of sports technique used in Yurchenko handspring vault by means of the macro methods for exercises learning during the training basic specialization stage. This scientific approach led to the organization of an experimental study, using the research methods as follows: 1. Method of theoretical and methodological analysis of literature related to artistic gymnastics. 2. Method of evaluation of gymnastics exercises sports technique using the algorithmic analysis of the motion. 3. Video computerized method, using" Pinnacle Studio"," Kinovea" and" Physics ToolKit" programs. 3. Method of movement postural orientation and evaluation of key elements of sports technique with complex coordination of movement structure. 4. Method of linear-branched programming of gymnastics exercises learning and improving. 5. Statistical method, by means of" KyPlot" program. The research was conducted from 2012 to 2014, when gymnasts` performances were monitored in three national competitions - handspring vaults event; a number of 7 athletes aged 12 to 15 participated in these competitions, all of them members of junior national team of Romania. The results of the research highlighted and identified the kinematic and dynamic characteristics of sports technique key elements of Yurchenko vault in women`s artistic gymnastics. The implementation of the macro methods of learning in young gymnasts` training contributed to the improvement of sports technique and the effective experimental distribution of the difficult and highly difficult basic vaults. ABSTRACT FROM AUTHOR